Analysis of factors influencing innovation and entrepreneurship education based on analytic hierarchy process - Xianchao Zhou; Yanbo Cheng (Glasnik Srpskog Geografskog Društva)
Innovation and entrepreneurship education (IEE) is a crucial pathway to enhance college students' innovation abilities and entrepreneurial spirit. This study employs the Analytic Hierarchy Process (AHP) to quantitatively analyze key factors influencing IEE in higher education, including policy support, teaching methods, teacher quality, student entrepreneurial motivation, and the external environment. The primary objective is to accurately calculate the weights of these factors and provide specific reference data. Our results show that government funding support is the most critical factor, followed by policy orientation, teaching methods, project-based learning, and teacher entrepreneurial experience. These five indicators account for 72% of the total weight of all factors. By quantifying the importance of these key factors through the AHP model, our findings validate existing research and offer specific scientific data for policy-making and teaching method optimization. This quantitative approach enhances the accuracy and reliability of results compared to previous studies, highlighting the importance of systematic and scientific analysis for understanding and optimizing complex educational systems. This study underscores the core role of government funding in IEE, providing new perspectives for future policy-making and educational strategies. It makes significant contributions to the field of IEE and emphasizes the importance of global educational innovation and reform.